An analysis of the study helps of doorwasys to reading - Jubida, Gloria Barros 1942- ([publisher not identified], 1967)
The study presents an analysis of some selections from "Doorways to Reading". The paper aims to answer the following: (1) To what extent do the study helps bring out the expected outcomes of the selection? (2) What specific reading skills are developed in the process of fully understanding a selection? (3) To what extent is each of the four dimensions of reading treated? (4) What exercises might help the readers realize the expected outcomes while developing a variety of skills in the four dimensions of reading?